A taguchi-SQP approach for minimizing energy per unit diesel production at crude distillation unit - Zainal-Abidin, M. (Trans Tech Publications Ltd, 2014)
Crude distillation unit (CDU) is one of the largest energy consumer units in a refinery. It consumes around 35-40 of the total process energy in refinery. This paper presents a systematic approach for selecting optimization variables using Taguchi method. These variables are subsequently employed in minimizing energy consumption per unit diesel production at CDU. A steady state model of the CDU was developed under the HYSYS 7.2 environment and utilized to demonstrate the efficacy of this method. Optimum energy consumption per unit diesel production obtained from Taguchi were validated by comparing the results with those obtained from HYSYS built-in SQP solver. The results reveal that the combination of Taguchi and SQP solver can reduce CPU time for optimization purposes. Â© (2014) Trans Tech Publications, Switzerland.